Dynamic Capabilities and Firm Effectiveness: The Mediating Role of Supply Chain Performance - Alica Grilec Kaurić; Dario Miočević; Josip Mikulić (Innovative Methods in Logistics and Supply Chain Management: Current Issues and Emerging Practices. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Dynamic capabilities (DCs) have been in the recent focus of mainstream strategy research. Recent theoretical advances have seen the advent of DCs in supply chain management research, where DCs have been identified as enhancers of supply chain performance and firm's effectiveness. However, the literature predominantly lacks studies that empirically integrate the DCs, supply chain performance and firm's effectiveness in single theoretical framework. Building on this gap in the literature, this paper investigates the interplay between DCs, supply chain performance and firm effectiveness. The study was carried out on a sample of 85 medium and large manufacturing firms in Croatia. This study contributes to the literature by offering empirical evidence that the DCs (agility, adaptability and alignment) higher value-added impact on firm's effectiveness in the presence of supply chain performance as a mediator. In the end, this study offers valuable theoretical and practical implications as well as suggestions for further research.
10419/209188; https://econpapers.repec.org/RePEc:zbw:hiclpr:19
Keywords: 650; dynamic capabilities; supply chain performance; companies' effectiveness; manufacturing industry